Persistent Oxygen Requirement beyond Prematurity: A Case of Acquired Pulmonary Vein Stenosis - Tyler A. Fick; Bernadette Richards; Carl H. Backes; Molly K. Ball (Hindawi Limited, 2017)
Acquired pulmonary vein stenosis is a rare cardiac defect and diagnosis can often be challenging, as many cases present with refractory or prolonged oxygen requirement over the expected course. Comorbid conditions can cloud this diagnosis further. Prognosis is poor for most patients. We present a case of idiopathic acquired pulmonary vein stenosis and discuss diagnostics, treatment options, and the need for further collaborative studies.